2021
DOI: 10.1515/revac-2021-0126
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhanced Raman scattering analysis with filter-based enhancement substrates: A mini review

Abstract: Surface enhanced Raman is a powerful analytical tool with high sensitivity and unique specificity and promising applications in various branches of analytical chemistry. Despite the fabrication of ingenious enhancement substrate used in laboratory research, the development of simple, flexible, and cost-effective substrate is also great important for promoting the application of SERS in practical analysis. Recently, paper and filter membrane as support to fabricate flexible SERS substrates received considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Particular advantages attributed to filter paper-based SERS are the ability to: create greater hot-spot sites, concentrate analyte, and ability to separate non-target molecules (if required). 16 Filter paper-based SERS substrates have recently shown strong capability in detecting trace amount of small molecules 16 while a cellulose-based substrate has been reported as a ESI † for SERS active NPs. 17 To our knowledge, this study is the first account of incorporating AuNPs on filter paper substrates that demonstrates the SERS capability with polystyrene nanoplastics (PSNPs).…”
mentioning
confidence: 99%
“…Particular advantages attributed to filter paper-based SERS are the ability to: create greater hot-spot sites, concentrate analyte, and ability to separate non-target molecules (if required). 16 Filter paper-based SERS substrates have recently shown strong capability in detecting trace amount of small molecules 16 while a cellulose-based substrate has been reported as a ESI † for SERS active NPs. 17 To our knowledge, this study is the first account of incorporating AuNPs on filter paper substrates that demonstrates the SERS capability with polystyrene nanoplastics (PSNPs).…”
mentioning
confidence: 99%
“…Polymer-based filter membranes show important features for these purposes, namely robust mechanical resistance and tuneable pore size. These membranes are available in various materials that allow sample concentration by large-volume filtration, promoting the target analyte uptake and, consequently, easier detection by SERS ( Xu et al, 2021b ). The lightweight and flexibility of membrane SERS substrates can also be combined with portable Raman spectrometers and smartphones, providing on-site detection ( Gao et al, 2016 ; Guo et al, 2019 ; Sun et al, 2021 ).…”
Section: Nanomaterials For Water Cleaning Nanotechnologiesmentioning
confidence: 99%
“…The Ag NPs paper substrate has been widely developed by the surface-enhanced Raman scattering spectroscopy (SERS) community, [23][24][25][26][27][28] and good detection sensitivity has been obtained. As for LIBS, Gondhalekar et al have reported a paperbased substrate coated with lanthanide markers, 29 which showed promising detection potential in biological analytes.…”
Section: Preparation and Characterization Of The Nelibs Substratesmentioning
confidence: 99%